Possibilities and concerns of implementing precision agriculture technologies on small farms in Slovenia - Rakun, Jurij; Rihter, Erik; Kelc, Damijan; Denis, Stajnko; Vindiš, Peter; Berk, Peter; Polič, Peter; Lakota, Miran (International Journal of Agricultural and Biological Engineering, 2022)
Precision agriculture (PA) through the use and utilization of innovative technologies is a concept in agricultural management that enables long-term efficiency gains, control of unforeseen changes, and a reduction of negative impacts on the environment. However, there are even more reasons and benefits to using precision agriculture technologies (PATs) on farms, but the actual use on small farms is often questionable. The main objective of this research was to evaluate and analyze the current state of PA and its potential on a set of small farms. In addition, a comparison was made between small farms located in less favored areas (LFAs) and more favored areas (MFAs) to find if specific characteristics of the surrounding environment affect the (non-) implementation of these technologies by farm owners, with respect to the given regional possibilities. The result shows that 57.5% of respondents on these farms have never implemented PATs before and 20% are beginners in their respective fields. It was found that there were no statistically significant differences in the integration between fewer LFAs and MFAs technologies and their use in this study. The majority of respondents believe that the main changes need to occur on the level of politics. The results show that the level of cost or initial investment is the main reason and the main obstacle in the implementation of PATs on the surveyed farms. Keywords: precision agriculture, small farm, technological innovations, implementation, situation overview, survey, ICT DOI: 10.25165/j.ijabe.20221503.6111 Citation: Rakun J, Rihter E, Kelc D, Denis S, Vindiš P, Berk P, et al. Possibilities and concerns of implementing precision agriculture technologies on small farms in Slovenia. Int J Agric & Biol Eng, 2022; 15(3): 16–21.